Comparing the Politicisation of EU Integration during the Euro and Schengen Crises - Leonard August Schuette (Journal of Contemporary European Research, 2019)
Although European integration has become an increasingly salient and controversial topic in domestic politics, the consequences of this politicisation of the European Union for the integration process have not received adequate scholarly attention. To fill this lacuna, this article devises five hypotheses on the effects of politicisation for the integration process, which are subsequently tested against the evidence of the Euro and Schengen crises. Both crises had comparable origins, but the Euro crisis caused substantial deepening of integration, while the Schengen crisis has not engendered any meaningful reforming steps. The empirical analysis finds that politicisation assumed different forms across the two crises, which is shown to be one causal factor that explains the variation in crises outcomes. The article thereby contributes to a multifaceted understanding of the politicisation of international institutions, EU integration theory and the dynamics of the Euro and Refugee Crises.